The absent-minded prisoner - Alexander Dilger (Universität Greifswald, Rechts- und Staatswissenschaftliche Fakultät, 1998)
If one of two rational players is absent-minded for at least three rounds, cooperation in a prisoners dilemma with a finite number of repetitions is possible. If both players are absentminded, even two rounds of absent-mindedness can be enough for cooperation in these rounds and all rounds before. Sufficient conditions for the existence of a cooperative equilibrium are derived, a plausible interpretation of absent-mindedness in the case of many repetitions is given.
Keywords: C72; 330; absent-mindedness; prisoners dilemma; repeated games